La rentabilidad de las grandes compañías como determinante en la elección de las BIG 4: Caso ecuatoriano 2012-2017 - Chávez, María Alexandra (2019)
The investigation is aimed at establishing the probability of large Ecuadorian companies to hire an audit firm considered in the financial world as BIG4. The dependent variable that is analyzed is a binary variable that, through a logit model, attempts to quantify the probability. The research is circumscribed within the neopositivist paradigm as defined by Kuhn. Therefore, the quantification of the return or independent variables are the profitability of large companies in Ecuador in the periods between 2012 and 2017. In the present investigation the logit model is used to establish the probability of contracting a BIG 4 as part of an entity through profitability indexes. As a result of the investigation, it was found that the entities' returns have a significant impact on the contracting of a BIG 4. Thus, it was concluded that companies that present a robust return have a high probability of contracting a BIG 4 and relieving financial information that is reliable and relevant to various users.